Management of Inventory for Firms Efficiency: A Study on the Manufacturing Industry in Johor - MOHD NOR, NORASMIHA; ISMAIL, FADILLAH (Research in Management of Technology and Business, 2023)
This study focused on how inventory management practices affect the efficiency of manufacturing firms. Therefore, the research objective of this study was to identify the relationship between Inventory Management Practices (IMPs) and Operational Efficiency (OE) of manufacturing firms. This research adopted four IMPs, which are Capacity Utilization (CU), Inventory Distribution Turnover (IDT), Inventory Automation (IA), and Lean Inventory (LI). This research applied quantitative approach and a survey was conducted by using questionnaire as research instrument. The questionnaires were sent through email to 500 manufacturing companies in Johor, and only 180 have been returned. A correlation analysis confirmed all four IMPs have a significant relationship with operational efficiency. It indicates that firm efficiency will improve by implementing these four inventory management practices. This research may provide a clearer view on how inventory management practices improve operational efficiency of manufacturing firms.